Overview of subjective well-being in educators at SMK X Sumba - Zamralita, Zamralita; Fahlevi, Reza; Sanjaya, Alvin; Amelia, Aulia Rizki (Privietlab, 2025)
Education is a fundamental right for all citizens, as outlined in the 1945 constitution. However, the equitable distribution of educational opportunities in Indonesia remains a significant challenge, particularly in regions such as East Nusa Tenggara (NTT) Province. This study aims to elucidate the subjective psychological well-being of educators at SMK X Sumba. The study employed a descriptive quantitative approach, leveraging a nonprobability sampling method through a convenience sampling technique. The subjective well-being of educators was measured using the Scale of Positive Affect and Negative Affect (SPANE) and Satisfaction with Life Scale (SWLS). The results showed that educators’ subjective well-being was classified as good, with 73.9% in the moderate category and 26.1% in the high category. Positive affection had a high level (95.7 %), while negative affection tended to be low (82.6 %). In terms of cognition, life satisfaction shows 87% of the respondents were in the high category, which reflects that educators at SMK X Sumba have positive feelings and high life satisfaction, although there is room for improvement. This suggests that educators should develop psychological wellbeing-based programs to support teaching quality and student learning outcomes.